The Ecological and Functional Significance of Mosses: A Comprehensive Overview - Marat , Nagmetullaev (Journal of Geosciences and Environmental Studies, 2024)
The article further expands on Moss Department's species' ecological roles in their habitats. These plants, through their reproductive mechanisms, contribute to the stability of ecosystems by interacting with pollinators and other organisms. The reproductive strategies, such as seed dispersal methods and the timing of flowering, are analysed, indicating how these plants adapt to various environmental conditions. In addition to their ecological importance, the article also examines certain species' cultural and historical significance within the Moss Department. Some plants have been used in traditional medicine, while others may hold symbolic value in various cultures. The economic contributions are elaborated, noting how these plants are used in pharmaceuticals, textiles, and even food production, depending on the species. The article paints a comprehensive picture of the Moss Department's importance from both a scientific and socio-economic perspective through a combination of botanical analysis, reproductive study, and economic insight.